2013
DOI: 10.4310/hha.2013.v15.n1.a15
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity at infinity for braid groups on complete graphs

Abstract: We show that the connectivity at infinity for configuration spaces on complete graphs is determined by the connectivity of chessboard complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In [MZ13], Meier and Zhang showed that the vertex links in the configuration spaces of r robots on the complete graph K r+N are homeomorphic to ∆ r,N . If a 0-cell v of Conf r (n, N ) corresponds to a configuration in which all robots are on the side of K n,N with n vertices, then the link of this 0-cell is the same as ∆ r,N as well.…”
Section: Remark 43 (Combinatorial Description Of Vertex Links) a 0-ce...mentioning
confidence: 99%
See 2 more Smart Citations
“…In [MZ13], Meier and Zhang showed that the vertex links in the configuration spaces of r robots on the complete graph K r+N are homeomorphic to ∆ r,N . If a 0-cell v of Conf r (n, N ) corresponds to a configuration in which all robots are on the side of K n,N with n vertices, then the link of this 0-cell is the same as ∆ r,N as well.…”
Section: Remark 43 (Combinatorial Description Of Vertex Links) a 0-ce...mentioning
confidence: 99%
“…Theorem 4.7 and Lemma 4.8 go a long way towards establishing much of our argument, particularly once we show that connectivity results about vertex links quickly lead to connectivity results about punctured vertex links, as is required by Theorem 1.2. A key fact about chessboard complexes is that they are vertex decomposible, and in Section 4 of [MZ13] this fact is used to prove that connectivity is preserved when any closed simplex is removed (Theorem 4.7 of [MZ13]).…”
Section: Remark 43 (Combinatorial Description Of Vertex Links) a 0-ce...mentioning
confidence: 99%
See 1 more Smart Citation